Novel immunotargets in multiple myeloma: biological relevance and therapeutic potential - Jana Kotulová; Klára Baďurová; Zuzana Chyra; Sabina Ševčíková; Nikola Garbová; Tomáš Jelínek; Roman Hájek; Matouš Hrdinka (Biomarker Research)
Abstract Multiple myeloma is a hematologic malignancy characterized by complex genetic and microenvironmental factors that drive disease progression and resistance to treatment. Despite advancements in therapies targeting established antigens, such as BCMA, CD38, SLAMF7, and GPRC5D, specific challenges persist, including antigen escape, treatment resistance, and off-tumor toxicity, highlighting the urgent need for novel therapeutic modalities. Recent advances in surface proteomics and integrative omics technologies have enabled the discovery of new surface antigens with the potential to address the challenges. By targeting antigens with higher tumor specificity and lower expression in healthy tissues, emerging immunotargets offer new avenues to minimize off-tumor toxicity and reduce the risk of relapse due to antigen loss or immune evasion. This review provides an overview of emerging immunotargets, summarizing their biological functions, roles in disease pathogenesis and immune evasion, and potential for therapeutic interventions. We focused on fifteen emerging targets currently in early clinical development or the preclinical phase, highlighting LILRB4, SEMA4A, ITGB7, CCR1, and CD70 as the most promising. These immunotargets demonstrate significant potential for next-generation immunotherapies, including antibody–drug conjugates, bispecific antibodies, and chimeric antigen receptor (CAR) T-cell therapies. Preclinical or early clinical studies show favorable safety profiles, high tumor specificity, and mechanisms to overcome immune resistance, collectively suggesting the potential for improved patient outcomes and reduced adverse effects. By presenting a comprehensive summary of these advances, this review underscores the translational potential of emerging immunotargets and provides insights to guide the development of innovative therapeutic approaches to improve outcomes for multiple myeloma patients.